Diversity of two forms of DNA methylation in the brain - Chen, Yuanyuan; Damayanti, Nur; Irudayaraj, Joseph; Dunn, Kenneth; Zhou, Feng C. (Frontiers in Genetics, 2014)
DNA methylation 5-methylcytosine (5mC) predicts a compacting chromatin inaccessible to transcription. The discovery of 5-hydroxymethylcytosine (5hmC), which is derived from 5mC, adds a new dimension to the mechanism and role of DNA methylation in epigenetics. Genomic evidence indicates that the 5hmC is located in the alternate regions to 5mC. However, the nature of 5hmC, as compared with classical 5mC remains unclear. Observing the mouse brain through embryonic development to the adult, first, we found that 5hmC is not merely an intermediate metabolite of demethylation, but is long lasting, chromatically distinct, and dynamically changing during neurodevelopment. Second, we found that 5hmC distinctly differs from 5mC in its chromatin affiliation during neural stem cell (NSC) development. Thirdly, , we found both 5mC and 5hmC to be uniquely polarized and dynamic through the NSC development. 5mC was found to progressively polarize with MBD1 and MeCP2, and recruits H3K9me3 and H3K27me3; while 5hmC progressively co-localizes with MBD3 and recruits H3K4me2. Critical differential binding of 5mC with MBD1, and 5hmC with MBD3 was validated by Resonance Energy Transfer technique FLIM-FRET. This transition and polarization coincides with neuroprogenitor differentiation. Finally, at the time of synaptogenesis, 5mC gradually accumulates in the heterochromatin while 5hmC accumulates in the euchromatin, which is consistent with the co-localization of 5hmC with PolII, which mediates RNA transcription. Our data indicate that 5mC and 5hmC are diverse in their functional interactions with chromatin. This diversity is likely to contribute to the versatile epigenetic control of transcription mediating brain development and functional maintenance of adult brain.